2010
DOI: 10.1007/s11064-010-0304-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Redox Homeostasis and Cellular Stress Response in Ménière’s Disease: Role of Vitagenes

Abstract: Ménière's disease (MD) is characterized by the triad of fluctuating hearing loss, episodic vertigo and tinnitus, and by endolymphatic hydrops found on post-mortem examination. Increasing evidence suggests that oxidative stress is involved in the development of endolymphatic hydrops and that cellular damage and apoptotic cell death might contribute to the sensorineural hearing loss found in later stages of MD. While excess reactive oxygen species (ROS) are toxic, regulated ROS, however, play an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 46 publications
4
70
0
1
Order By: Relevance
“…Furthermore, the serum concentration of reactive oxygen species (ROS; as measured using spectrophotometric methods) and a global oxidative stress index, which reflect oxidative and antioxidant counterparts, respectively, were significantly higher in patients with SSNHL than they were in controls (Capaccio et al, 2011). Increased levels of protein carbonyls and 4-hydroxynonenal, which are markers of protein oxidation, have been detected in the lymphocytes of patients with Ménière's disease compared with controls, with a significant decrease in the ratio of reduced glutathione versus oxidized glutathione both in the plasma and in lymphocytes (Calabrese et al, 2010). The results of these previous reports imply that the oxidative stress response is involved in the pathophysiology of both SSNHL and Ménière's disease.…”
mentioning
confidence: 90%
“…Furthermore, the serum concentration of reactive oxygen species (ROS; as measured using spectrophotometric methods) and a global oxidative stress index, which reflect oxidative and antioxidant counterparts, respectively, were significantly higher in patients with SSNHL than they were in controls (Capaccio et al, 2011). Increased levels of protein carbonyls and 4-hydroxynonenal, which are markers of protein oxidation, have been detected in the lymphocytes of patients with Ménière's disease compared with controls, with a significant decrease in the ratio of reduced glutathione versus oxidized glutathione both in the plasma and in lymphocytes (Calabrese et al, 2010). The results of these previous reports imply that the oxidative stress response is involved in the pathophysiology of both SSNHL and Ménière's disease.…”
mentioning
confidence: 90%
“…Staroń et al [41] found that rheumatoid arthritis (RA) patients have higher ROS levels than healthy people, whereas the expression of the antioxidant enzymes catalase and GPx were not significant different, and that superoxide dismutase antioxidant activity and -SH levels were lower in RA patients than in the control group. The GSH:GSSG ratio was significantly (P < 0.05) decreased in the plasma and lymphocyte cells of patients with Ménière's disease [42].…”
Section: Gsh-related Diseasesmentioning
confidence: 86%
“…[12] In Meniere's disease, the patient's plasma and lymphocyte oxide glutathione amounts were found to be higher than the reduced glutathione amount. [13] In the GPX1 codon 200 C/T polymorphism, the balance between oxidative stress and antioxidants failed, and this was thought to be the reason for many diseases, such as cancer, Alzheimer's etc. [14,15] In noise-induced hearing loss and idiopathic sudden hearing loss, investigating the effect of oxidative stress included studying various enzyme polymorphisms, and some relationships between the gene polymorphisms and the diseases were found.…”
Section: Discussionmentioning
confidence: 99%